2001
DOI: 10.1046/j.1526-0968.2001.00375.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lymphocyte Depletion and Clinical Effectiveness on Filtration Leukocytapheresis in Patients with Rheumatoid Arthritis

Abstract: We evaluated the relationship between the clinical benefit of filtration leukocytapheresis (LCP) and the number of removed leukocytes in patients with rheumatoid arthritis (RA). LCP was performed in 31 drugresistant RA patients. LCP was carried out 3 times with 1 week separating each session. Assessment of RA before and after LCP showed a substantial and rapid improvement in tender joint counts, swollen joint counts, and patients' and physicians' assessments. Careful analysis indicated that 19 of 31 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Ueki et al. reported that the lymphocyte elimination rate was higher in responders (18). Recently, Eguchi et al.…”
Section: Discussionmentioning
confidence: 96%
“…Ueki et al. reported that the lymphocyte elimination rate was higher in responders (18). Recently, Eguchi et al.…”
Section: Discussionmentioning
confidence: 96%
“…Numerous therapeutic strategies to treat RA have been designed, based on pathogenesis associated with T cells. Thoracic duct drainage, total lymphoid irradiation (34), lymphocytapheresis (35,36), and anti-T cell Abs (37,38) are examples of therapeutic manipulations for blocking or depleting T cells. Although T-celltargeted therapies alleviate RA initiation and pathogenesis in animal models (8,18), clinical trials to date suggest no remarkable benefits (21,39).…”
Section: Discussionmentioning
confidence: 99%
“…LCAP has been reported as an effective treatment in RA and ulcerative colitis [10][11][12][13]. The mechanism of LCAP in inflammatory diseases is speculated to be through removal of activated WBCs and platelets [13][14][15][16]. Decrease of inflammatory cytokines and increase of anti-inflammatory cytokines after LCAP was reported [17][18][19].…”
Section: Introductionmentioning
confidence: 99%